Preparation and characterization of PES/SiO2 composite ultrafiltration membrane for advanced water treatment - Muhamad, Mimi Suliza (Springer New York, 2015)
Polyethersulfone (PES) is a commonly used polymeric material for the fabrication of ultrafiltration (UF) membranes. However, the hydrophobic nature of PES leads to poor membrane performance with low anti-fouling properties during filtration process. Hence, for this study, the PES-based hollow fiber membrane was modified with inorganic silicon dioxide (SiO2) nanoparticles of various loading (from zero to 4 wt%), aiming to improve the membrane properties for advanced water treatment process. The characterization of the surface morphology, physical and chemical properties of novel PES/SiO2 composite membranes was performed by SEM, FTIR-ATR, TGA and contact angle analyzer. The SEM images show the changes in membrane structure as well as skin layer thickness upon addition of SiO2 nanoparticles. The FTIR-ATR analysis shows the functional group of SiO2 in the polymer matrices. Results further show that the presence of 2 wt% SiO2 in the membrane matrix is the best loading to improve the water flux and bovine serum albumin (BSA) rejection, achieving 87.2 L/m2·h and 94%, respectively. As a comparison, the control PES membrane only exhibits water flux of 44.2 L/m2·h and rejection of 81%. Results also show that the flux recovery percentage of the membrane was improved from 82% in the control membrane to 93% in the membrane incorporated with 2 wt% SiO2, indicating improved membrane anti-fouling property. Furthermore, the PES/SiO2 membrane shows huge potential for advanced water treatment, as the qualities of the permeate samples treated by this membrane could meet the limit set by a local water company.